Wavelength Shift Measurement Method Without Use of Spectrometer: The New Way for Environment Photonic Sensors - Hoi, Pham Van; Van, Nguyen Thuy; Dai, Pham Van; Thang, Le Huu; An, Nguyen Van; Binh, Pham Thanh (Communications in Physics, 2018)
The photonic sensors have shown very effectively for measuring the toxic contents in the liquid and air environments. In principle, the photonic sensors based on measurement of wavelength shift between reference condition and testing environments that we need use the spectrometer with high cost. In this paper, we present new configurations of photonic devices for measuring wavelength shift without use of spectrometer, which has a large potential for application in sensing technique with low cost. There are two configurations of photonic sensors are presented: i) first of them is based on fiber Bragg grating (FBG) combined with DFB laser diode with controlling wavelength emission by laser temperature and ii) second one is used  the fiber ring laser from Erbium-doped fiber and two FBG operated as  reference and sensing probe. The etched-fiber Bragg grating (e-FBG) as sensing probe is suitable for bio- and/ or chemical sensors. A novel photonic sensor can increase sensitivity and measuring accuracy of device by the narrow line-width of reflection spectra from laser and the sensor can determine a refractive index variation of 2x10-4, which is similarly for high resolution spectrometer. The experimental results show that this sensing method could determine different mixing ratios of organic solvents in liquid environment with good repeatability, high accuracy and rapid response.Keywords: